The Influence of Islamic Financial Literacy, Income, and Lifestyle on Financial Management among Housewives - Hanifa Qotrunnada Hayyi; Aminah Nuriyah (Universitas Darussalam Gontor, 2024)
This research discusses the influence of Islamic financial literacy, income, and lifestyle on financial management among housewives (a case study in Jabodetabek). The research adopts a quantitative approach using Multiple Linear Regression method, focusing on a case study in Jabodetabek. The data for this study were collected through questionnaires distributed to respondents who are Muslim housewives with income. The findings of this research are as follows: 1) Islamic financial literacy does not have a significant influence on financial management among housewives. 2) Income has a significant influence on financial management among housewives. 3) Lifestyle has a significant influence on financial management among housewives. 4) Islamic financial literacy, income, and lifestyle collectively have an influence on financial management among housewives.